2011
DOI: 10.1016/j.surfcoat.2011.04.076
|View full text |Cite
|
Sign up to set email alerts
|

Wear resistance enhancement of the titanium alloy Ti–6Al–4V via a novel co-incident microblasting process

Abstract: Publication informationSurface and Coatings Technology,: 4941-4947Publisher Elsevier Item record/more information http://hdl.handle.net/10197/5258 Publisher's statementThis is the author's version of a work that was accepted for publication in Surface and Coatings Technology. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…The surface-modified Ti6Al4V substrate has a greater surface roughness than the non-surface-modified surface roughness. This results is very similar to reference [7]. Surface modification (micro-powder blasting) increases the surface roughness of Ti6Al4V substrate.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The surface-modified Ti6Al4V substrate has a greater surface roughness than the non-surface-modified surface roughness. This results is very similar to reference [7]. Surface modification (micro-powder blasting) increases the surface roughness of Ti6Al4V substrate.…”
Section: Resultssupporting
confidence: 91%
“…The results indicate that the surface roughness of Ti6Al4V increased with the increase of Al 2 O 3 particle size. The surface roughness of the Ti6Al4V substrate of SiC impact particles exceeded higher than the surface roughness of Al 2 O 3 impact particles of the same size This results is very similar to reference [7]. Surface modification (micro-powder blasting) increases the surface roughness of Ti6Al4V substrate.…”
Section: Surface Roughnesssupporting
confidence: 84%
See 1 more Smart Citation
“…The antibacterial effectiveness of Ti substrate treated with pure HA particles or HA combined with zinc apatite (ZnA), silver apatite (AgA), or strontium apatite (SrA) particles were evaluated, and it was found that the substrate that was treated with HA and AgA performed best in this respect [5]. The wear and friction of a TiAl 6 V 4 substrate that was combined with Al 2 O 3 and teflon, silicon carbide (SiC), or boron carbide (B 4 C) by blasting method was investigated [6]. An MG63 cell culture was conducted on a Ti substrate after blasting with HA and sintered CaP particles.…”
Section: Introductionmentioning
confidence: 99%
“…Titanium (Ti) and its alloys are preferred in orthopedic applications when the implant material is in direct contact with bone. These materials possess excellent corrosion resistance, low toxicity, “acceptable” compatibility with the living tissue, and good mechanical properties, namely high tensile strength and durability, high ductility, and low density. ,, One drawback, however, is the possible aseptic loosening due to inadequate tissue response (i.e., fibrous tissue formation and/or infection) and integration of the implant . One of the approaches to address these problems is to chemically modify the surfaces of the implant, such as by grafting of bioactive polymers onto Ti substrates to create biomimetic surfaces.…”
Section: Introductionmentioning
confidence: 99%